Arsitektur Perusahaan Untuk Mendukung Transformasi Digital: Systematic Literature Review - Wahyunia Ningsih Syam; Bambang Soedijono W.A; Alva Hendi Muhammad (Jurnal Informatika dan Komputer, 2023)
This study aims to describe the development of studies on Enterprise Architecture (EA) in supporting Digital Transformation. The Systematic Literature Review (SLR) method was used to obtain 36,513 studies with manual searches in two databases, and finally 12 primary studies were selected with a time limit of 2018-2022. A total of seven issues/issues were identified and analyzed, namely EA support analysis, EA weakness analysis, Enterprise Architecture Management (EAM) benefit analysis, EA evolution, EA method development, and EA model development. EA's contribution is explained with a description of the problems / issues that have been identified, and the research sectors analyzed include Small and Medium Enterprises in Mechanical Engineering, manufacturing, health, and Small and Medium Enterprises in general, and some studies that do not limit their research sectors. The results show that studies on EA in supporting Digital Transformation have decreased in the last five years. Studies related to the benefits of EAM still show EA's weakness in supporting Digital Transformation. The limited research sector consists of SMEs and health. This review provides some guidelines for future researchers who want to research on this topic.